(untitled) (Fiep Bulletin - online, 2013)
This thesis deals with the self-knowledge importance and corporal practices and the contribution of the Transpersonal Education for the initial formation process of students of Physical Education. In this context, students are stimulated to come in contact with the bases of learning to know, to make, to live together and to be for the promotion of integral education. This work presents tracks for the teacher formation of Physical Education. It deals with the unfolding of teaching experiences in 2006, in Graduation Course in Physical Education of Universidade Federal do Rio Grande do Norte, in subject of Corporal Conscience, offered to undergraduate students which can be characterized as an action-research. This process was chosen as knowledge and intervention method because it allowed knowing and acting at the same time, studying the conditions and results of accomplished experience. In shared meetings with reflected experiences, we appeal to the experiences of situations that had mobilized the corporal, emotional, mental and spiritual dimensions of participants. The data collected through observations, accounts, questionnaires and interviews of learning processes had been starting points for the beginning of dialogue along with students of Graduation Course in Physical Education. The findings had been interpreted through of hermeneutics and discourse analysis. In this research, participants are considered as protagonist and boosters of educative process. The theoretical basis was supported by Transpersonal Education which contributed for a peace culture and respectful relationship. In its initial formation process, this research protagonists had evidenced of the importance of transpersonal education, geared toward action and changing, new ways of being and living together, facing the daily conflicts from a human and rational perspective. The research emphasized the importance of a new look on the teacher formation of Physical Education to face the limits of fragmented formation.